Highly secured Android based smartphone - Zhao, Kun (2017)
In the recent years, the amount of data transmitting between devices become sufficiently large. Thus, information security becomes a big concern. With great improvements in data accessibility, the risks in data breach also give us worries. In this report, analysis on the effectiveness of AES algorithm in Android operating system defending Side Channel Attack will be illustrated. To assess the capability of AES algorithm, firstly it is implemented into an Android app which allow users to encrypt and decrypt text using AES algorithm. Secondly, by using Cloud Server or Bluetooth, cipher text can be transmitted between different mobile devices. Thirdly, the EMA attack on mobile devices are planned to be carried out. But, because of constrain in the existing attacking system and the complexity in attacking mobile devices, the attack is not successful. While, studies on topic of DPA attack, EMA attack targeted on mobile devices and different countermeasures are carried out. In the app development, two android app are developed. They have function in authentication, AES-128 encryption, AES-128 decryption, data transmitting via WiFi and Bluetooth individually, data storage and auto processing. Apps developed are compactable with android operating system 5.0 and above. It provides completed testing environment for EMA attack with different transmitting media. In the research part, topics of power analysis, differential power analysis and countermeasures in software against DPA attack are presented. In dealing with the challenges in EMA attack process, research on EMA attack on mobile devices are carried. The challenges and possible solutions are illustrated in detail in chapter nine.